Queer Data Studies - Patrick Keilty, Rebecca Herzig, Banu Subramaniam (Feminist Technosciences, 2024)
Data, perilous and powerful, is both a worldmaking and a dismantling force. The collection of data about queer lives and bodies, the consequences of data analysis for queer subjects, and considerations of privacy and consent often present ethical dilemmas even as queer data expands our understanding of who and what counts. The need for queer analyses and perspectives has taken on a new sense of urgency in light of hostile antiqueer policies by major technology companies, the security theater of airports, the disproportionate rates of policing queer people and people of color, digital surveillance in border security, and the proliferation of digital health records. Gathering wide-ranging interdisciplinary conversations into one rich volume, Queer Data Studies challenges readers to rethink how the extraction, circulation, modeling, governance, and use of data affects queer subjects and, at the same time, to consider how the power of data might be harnessed in the service of queer ethics. Contributors take a capacious approach to data, drawing from a range of sources, including stories, sounds, medical data, police data, maps, and algorithmic modeling. This anthology engages intersectional, decolonial, feminist, queer, and trans research, advancing ongoing dialogues about data across the social sciences, humanities, and applied sciences.